COMPARISON OF ECONOMIC STATUS AND EDUCATIONAL STATUS OF PARENTS ON FINE MOTOR DEVELOPMENT IN CHILDREN AGED 24 MONTHS IN THE CHILD POLY OF RSUD Dr. ADJIDARMO - Ermi Rosmayanti; Resi Galaupa (Lembaga Pengembangan Kinerja Dosen, 2023)
Delay in early childhood development is high in all countries, this condition is more common than other chronic conditions that cause major morbidity throughout life. This incident is evidenced by the incidence of child development delay problems in the world in 2015 around 12-16%, in Asia 50% and in Africa as much as 30%. The purpose of this study was to compare the economic status and educational status of parents on fine motor development in toddlers aged 24 months at the children's polyclinic at ADJIDARMO Hospital in 2022. This research method used an analytic survey with a cross-sectional design. The sample in this study were toddlers aged 24 months as many as 82 respondents, the sampling technique was accidental sampling. Data analysis using chi square. The results showed that there was a significant relationship between education (0.026 <0.05), economic status (P-Value <0.040) and fine motor development in toddlers aged 24 months at the Children's Clinic of Dr. ADJIDARMO in 2022 with (Pvalue < α).So that this research is expected to be able to provide education and information Fine Motoric Development in Toddlers.